(untitled) (Baltic Journal of Sport and Health Sciences, 2023)
In team sports like soccer, the ability to make quick decisions is essential for successful performance. Players must perceive and understand the available aﬀordances in their environment to eﬀectively utilize the information and make accurate decisions on the feld. Visual exploratory actions play a crucial role in acquiring the necessary information, allowing players to anticipate action possibilities and plan their subsequent actions. This study aimed to evaluate the eﬀectiveness of an innovative training protocol based on visual exercises in improving soccer-specifc motor skills of U12 soccer players. Thirty young male soccer players participated in the study and were randomly assigned to one of three groups: Technique Group (T-G), Visual-Technique Group (VT-G), and Control Group (C-G). The T-G received technical training, the VT-G received the same training with the addition of visual stimuli, and the C-G received regular in-season training. Pre- and post-test measurements were conducted on soccer-specifc motor skills. The results showed that the VT-G demonstrated signifcant improvements in motor skills compared to the T-G and C-G. These fndings suggest that incorporating targeted visual training into soccer training programs can enhance perceptual-cognitive and visual skills, leading to improved agility and overall on-feld performance. Keywords: soccer, agility, visual training, youth sports, motor skills.